2012
DOI: 10.1007/s10853-012-6705-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nanotube surface oxidation on the electrical properties of multiwall carbon nanotube/poly(vinylidene fluoride) composites

Abstract: Carbon nanotubes / poly(vinylidene fluoride) composites were prepared using CNT with different oxidation and thermal treatments. The oxidation procedure leads to CNT with the most acidic characteristics that lower the degree of crystallinity of the polymer and contribute to a large increase of the dielectric constant. The surface treatments, in general, increase percolation threshold and decrease conductivity, but, on the other hand, are able to promote the nucleation of the electroactive phase of the polymer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 49 publications
(76 reference statements)
2
17
0
Order By: Relevance
“…In particular, compared with other spherical-shaped conductive filling materials such as carbon black, MWCNTs with large length/diameter aspect ratios help the composite system show a high electric conductivity at low concentrations due to their low percolation threshold [47,48]. However, Carabineiro et al [49] observed that the conductivity of the PVDF-MWCNTs further increased by nearly three orders of magnitude, from order of 10 −7 S/cm to order of 10 −4 S/cm, by the increased concentration of the MWCNTs. Figure 8 shows typical galvanostatic discharge of PVDF-PAN/MWCNTs with different currents and wt.% of MWCNTs.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, compared with other spherical-shaped conductive filling materials such as carbon black, MWCNTs with large length/diameter aspect ratios help the composite system show a high electric conductivity at low concentrations due to their low percolation threshold [47,48]. However, Carabineiro et al [49] observed that the conductivity of the PVDF-MWCNTs further increased by nearly three orders of magnitude, from order of 10 −7 S/cm to order of 10 −4 S/cm, by the increased concentration of the MWCNTs. Figure 8 shows typical galvanostatic discharge of PVDF-PAN/MWCNTs with different currents and wt.% of MWCNTs.…”
Section: Resultsmentioning
confidence: 99%
“…The materials used were Viton GF-600S fluoroelastomer, FE; organic peroxide, Luperox 101 XL-45; acid surface modified carbon nanotube MCNT (TNMC8, -COOH Content:0.49wt%), carbon nanotube CNT (TNM8) both with an outside diameter > 50 nm, inside diameter:5-15nm, purity > 95%, and length [10][11][12][13][14][15][16][17][18][19][20] Mixing FE with additives was done using a laboratory scale two roll mill with a roll temperature of 48°C. FE in the above mentioned composition was supplied to the open roll.…”
Section: Materials and Compounding Proceduresmentioning
confidence: 99%
“…Carabineiro et al [19,20] prepared CNT/PVDF composites using modified CNT samples. According to their research results, surface modifications of MWCNTs had an effect on the electrical response and the degree of crystallinity of the CNT/PVDF nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent work, reduced graphene oxide (GO)-ZnO was synthesized and added into PVDF to produce a completely flexible thin film. [22] They showed that because of the inclusion of the nanofillers in host, PVDF matrix can lead to increasing of β-phase and as a consequence increase of piezoelectricity and thermal stabilization of polymers during their decomposition. Wu et al showed in their study the superior dielectric performance of the GO/PVDF composites are demonstrated.…”
Section: Introductionmentioning
confidence: 99%